La tradizione classica nei "Sonetti et canzoni" di Iacopo Sannazaro (Quaderni di Gargnano, 2020)
This paper deals with the issue of Sannazaro’s lyric poetry’s sources, with a focus on the intertextual links with the classical literature. Although there are a few studies on the relationship between some poems and the latin poetry, a thorough study of the question is still lacking and the sources of the Sonetti et canzoni have not been duly investigated. As a result the image of Sannazaro’s lyric that we have is not entirely accurate, in so much as it places too much emphasis on the indebtedness to Petrarch’s Fragmenta. On the ground of a systematic filing of the classical sources this paper demonstrates their importance, especially on the level of inventio, by showing Ovid’s role for understanding the architecture of the second half of the princeps and the peculiarities of Sannazaro’s love poetry, and the uses of classics in political and encomiastic texts. Specifically, on the second front, the paper draws attention to the depiction of Ferrandino as a new Enea, and the relationship to the panegyrical tradition as a reflex of the dialogic character of Renaissance’s culture. Il contributo tratta la questione delle fonti della poesia lirica di Sannazaro, concentrandosi sui legami intertestuali con la letteratura classica. Benché vi siano alcuni studi sulla relazione tra singoli testi e la poesia latina, manca ancora una ricerca approfondita sull’argomento e le fonti dei Sonetti et canzoni non sono state indagate come meriterebbero. Da ciò discende che l’immagine della lirica di Sannazaro che possediamo non sia del tutto accurata, in quanto pone troppa enfasi sui debiti nei confronti dei Fragmenta di Petrarca. Sulla base di una schedatura sistematica delle fonti classiche, il saggio dimostra la loro importanza, specialmente sul piano dell’inventio, mettendo in luce il ruolo di Ovidio per la comprensione dell'architettura della seconda metà della princeps e le peculiarità della poesia amorosa di Sannazaro, e gli usi dei classici nei testi politici ed encomiastici. In particolare, sul secondo fronte, il lavoro richiama l'attenzione sulla rappresentazione di Ferrandino come nuovo Enea, e sul rapporto con la tradizione dei panegirici come riflesso del carattere dialogico della cultura rinascimentale.
Keywords: Sannazaro; Sonetti et canzoni; tradizione classica; Ovidio